Association of Ligamentous Laxity, Male Sex, Chronicity, Meniscal Injury, and Posterior Tibial Slope With a High-Grade Preoperative Pivot Shift: A Post Hoc Analysis of the STABILITY Study. Issue 4 (31st March 2021) - Batty, Lachlan M.; Firth, Andrew; Moatshe, Gilbert; Bryant, Dianne M.; Heard, Mark; McCormack, Robert G.; Rezansoff, Alex; Peterson, Devin C.; Bardana, Davide; MacDonald, Peter B.; Verdonk, Peter C.M.; Spalding, Tim; et al.
Background: A spectrum of anterolateral rotatory laxity exists in anterior cruciate ligament (ACL)–injured knees. Understanding of the factors contributing to a high-grade pivot shift continues to be refined. Purpose: To investigate factors associated with a high-grade preoperative pivot shift and to evaluate the relationship between this condition and baseline patient-reported outcome measures (PROMs). Study Design: Cross-sectional study; Level of evidence, 3. Methods: A post hoc analysis was performed of 618 patients with ACL deficiency deemed high risk for reinjury. A binary logistic regression model was developed, with high-grade pivot shift as the dependent variable. Age, sex, Beighton score, chronicity of the ACL injury, posterior third medial or lateral meniscal injury, and tibial slope were selected as independent variables. The importance of knee hyperextension as a component of the Beighton score was assessed using receiver operator characteristic curves. Baseline PROMs were compared between patients with and without a high-grade pivot. Results: Six factors were associated with a high-grade pivot shift: Beighton score (each additional point; odds ratio [OR], 1.17; 95% CI, 1.06-1.30; P = .002), male sex (OR, 2.30; 95% CI, 1.28-4.13; P = .005), presence of a posterior third medial (OR, 2.55; 95% CI, 1.11-5.84; P = .03) or lateral (OR, 1.76; 95% CI, 1.01-3.08; P = .048) meniscal injury, tibial slope >9° (OR, 2.35; 95% CI, 1.09-5.07; P = .03), and chronicity >6 months (OR, 1.70; 95% CI, 1.00-2.88; P = .049). The presence of knee hyperextension improved the diagnostic utility of the Beighton score as a predictor of a high-grade pivot shift. Tibial slope <9° was associated with only a high-grade pivot in the presence of a posterior third medial meniscal injury. Patients with a high-grade pivot shift had higher baseline 4-Item Pain Intensity Measure scores than did those without a high-grade pivot shift (mean ± SD, 11 ± 13 vs 8 ± 14; P = .04); however, there was no difference between groups in baseline International Knee Documentation Committee, ACL Quality of Life, Knee injury and Osteoarthritis Outcome Score, or Knee injury and Osteoarthritis Outcome Score subscale scores. Conclusion: Ligamentous laxity, male sex, posterior third medial or lateral meniscal injury, increased posterior tibial slope, and chronicity were associated with a high-grade pivot shift in this population deemed high risk for repeat ACL injury. The effect of tibial slope may be accentuated by the presence of meniscal injury, supporting the need for meniscal preservation. Baseline PROMs were similar between patients with and without a high-grade pivot shift.